Metodologi Ilmu Ekonomi Islam Monzer Kahf - Ahmad Ubaidillah (JES (Jurnal Ekonomi Syariah), 2018)
Science, including Islamic economics, is a systematic knowledge acquired in certain ways agreed upon by scientists. Certain ways to acquire such schematic knowledge are called methodologies. Science is obtained through investigation or investigation. But not every investigation can be called a legitimate and recognized way to gain the knowledge. Science has certain ways or processes called research. Thus, the methodology is in fact the ways or scientific research techniques. The technique here means ways of conducting an investigation and assessing the findings or evidences, ie judging whether the finds are true or false. After seeing how important the methodology is in building a discipline, especially the discipline of Islamic economics, this paper will try to answer the question: how is the methodology offered by Monzer Kahf to build Islamic economics? The research method used in this research concerns types, approaches, sources and data types, data collection techniques, data analysis techniques. The type of this research is library research, namely research conducted by taking and collecting data from the literature related to the issues discussed. Sources of research data obtained are from the existing literature, by collecting primary and secondary data. Primary data in this study refers to the books and other research journals by Monzer Kahf. The secondary data in this research is obtained from books, magazines, journals, articles, and so forth, written by other writer. Analytical technique used is descriptive-analytical analysis method. The results show that the task of describing the Islamic economic system consists of two parts. First, Islamic economists have to find the theory of the components of the economic system and its internal relations. Second, they are to investigate the economic validity and power of the system. Essentially, the approach used to find the Islamic economic system is similar to the approach used to find the general theories and rules of fiqh. Economics as one of the social sciences needs to develop a path to history to explore its experiences and determine the direction of long-term economic life. Islamic economists must revise conventional economic theory to recognize and separate biased postulates. In other words, refining theories is full of the dogmatic, doctrinal, and moral views of the experts and the environment. Keywords: Islamic Economics, Methodology, Monzer Kahf